Asian redtail catfish (Hemibagrus nemurus) larvae response to commercial feed enriched with fish oil derived from Pangasius waste - Aryani Netti; Suharman Indra; Heltonika Benny; Edison Edison; Yulindra Ade; Stefani Natasya (BIO Web of Conferences)
Asian redtail catfish (Hemibagrus nemurus) is a freshwater commodity that has been cultivated and has high economic value. Feed is one of the important factors in cultivation. Larvae favor good quality feed and will increase their growth. Feed enrichment with fish oil will improve palatability and stimulate growth. One method to improve feed quality is to enrich it with fish oil derived from Pangasius processing waste. The purpose of the study was to determine the response and growth of Asian redtail catfish larvae to feed that had been enriched with oil derived from Pangasius processing waste at different doses. The treatments used were P1 = commercial feed without enrichment, P2 = feed enrichment with 8% fish oil, P3 = feed enrichment with 10% fish oil, P4 = feed enrichment with 12% fish oil, and P5 = feed enrichment with 14% fish oil, which was reared with a stocking density of 5 fish/L. The results showed that feed enrichment with oil derived from Pangasius processing waste influenced the feeding response of the Asian redtail catfish larvae with the best treatments P3 and P4 with a value of 9.0, while the best growth and survival was P3 (0.87 ± 0.00 and 82.33 ± 2.08). In conclusion, feed enrichment with a 10% dose gives the best response and effect on the growth of Asian redtail catfish larvae.